PENGARUH LIVING COST, TEMAN SEBAYA, DAN LINGKUNGAN SOSIAL TERHADAP PERILAKU KONSUMTIF MAHASISWA: Indonesia - Nur Laelis Naeni; Yopi Nisa Febianti (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
This study aims to determine the effect of living costs, peers and the social environment on student consumptive behavior. This study uses a quantitative approach to the survey method. The number of samples is 74 respondents taken by probability sampling technique and simple random sampling. Data analysis technique using multiple linear regression. The results of this study indicate: 1) there is a negative and significant effect of lifestyle on students' consumptive behavior 2) there is a positive and significant influence of peers on students' consumptive behavior 3) there is a positive and significant influence of the social environment on students' consumptive behavior 4) there is an influence positive cost of living, peers and social environment together on student consumptive behavior. The test results for the coefficient of determination obtained Adjusted R Square of 0.893 which indicates that the effect of the cost of living, peers, and the social environment on student consumptive behavior is 89.3% while the remaining 10.7% comes from other variables not examined in this study.